Impact of APOE4 Burden on Intracortical Myelination in Cognitively Healthy Individuals - Karppinen, Jenni (My University, 2025)
Alzheimer´s Disease (AD) is associated with a greater loss of myelin integrity than in normal ageing. Demyelination may be an early biomarker along with the primary AD pathology (Amyloid-beta plaques and neurofibrillary tangles of tau protein). APOE ε4 genotype (APOE4) is the strongest genetic risk factor for sporadic AD. Whilst several studies have proposed that APOE4 may impact myelination, few studies have investigated this effect in human populations. The purpose of the present study was to assess whether there are differences in intracortical myelination in cognitively unimpaired (CU) APOE4 homozygotes (E4/E4), heterozygotes (E3/E4), and non-carriers (E3/E3 or E3/E2). Myelination within cortical grey matter was measured using mean T1w/T2w ratio (mT1w/T2w). Participants were CU older individuals (n = 103; E4/E4 = 20; E3/E4 = 41; E3/E3 or E3/E2 = 42). Differences among the three groups, based on APOE genotype, were evaluated through whole brain analysis and in 48 selected Regions of Interest (ROI) using ANCOVA, with age, sex, and scanner type as covariates. There was no significant difference in mT1w/T2w between genotypes in the whole brain analysis (p > 0.05 False Discovery Rate; FDR). ROI analysis found a significantly higher mT1w/T2w in APOE4 heterozygotes than in non-carriers in the right transverse temporal gyrus (ANCOVA: F (2, 95) = 3.92, p = 0.023 unc.; Tukey’s HSD: p = 0.007, 95% C.I. = -0.122 to -0.016) but this difference did not survive corrections for multiple comparisons (p = 0.476 FDR). There were no significant pairwise differences between homozygotes and heterozygotes or between homozygotes and non-carriers in this region. Higher mT1w/T2w in the temporal region in APOE4 heterozygotes suggests greater myelination in this area in heterozygotes, which is in the opposite direction than predicted. However, this finding did not survive correction for multiple comparisons. This also contradicts previous findings, which showed lower myelination in this area in APOE4 carriers. This may be explained by methodological limitations in using mT1w/T2w ratio as a measure of myelination, the CU study population and the relatively small sample size. We did not find differences among the APOE groups in myelin integrity. However, further investigation is required using a larger sample size to better assess the impact of APOE4 burden on myelination using mT1w/T2w ratio.
Keywords: APOE4, T1w/T2w ratio, myelination, Alzheimer’s disease, MRI.